ANALISIS TINDAK TUTUR ILOKUSI BAHASA HUMOR DALAM KUMPULAN CERITA ABU NAWAS - Ratna Lita Sari Lita Sari; M. Nur Mustafa Mustafa; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This  research is titled analysis of illocutionary speech act of the humor language in Abu Nawas stories collection. Problems examined in this research is illocutionary speech acts contained in  Abu Nawas stories. This research were used a qualitative and descriptive method. Data were collected by using documentation techniques. However, the finding of this study showed five forms of illocutionary speech act, the five forms of illocutionary speech act were assertive speech act which contains of informing, proudly, sighing demanding and reporting. Directive speech act were consists of commanding, asking, requesting, ordering and threatening. Commissives speech act which involves promising, bargaining and praying. Expressive speech act that consists of observing, expressing thanks, insulting, praising, and congratulating. declarative speech act consists of surrendering, divorcing, freeing, expelling, indicating and verdicting. Key word: speech act, speech act illocution, assertive, directive, Commissive, expressive, declarative.